Molecular identification of Hypomyces chrysospermus mycoparasitic fungus isolated from mushrooms in a local market of Iraq - Noor Talib Hamdan (Journal of the Pakistan Medical Association, 2024)
In this study, mycoparasitic fungus was identified by using the rDNA internal transcribed spacer barcode marker, i.e. ITS rDNA gene. Amplicons were sequenced and identified by NCBI – BLAST (Basic local alignment search tool). The BLAST results revealed that NOOR strain matched 100% with accession numbers [MH854754.1]. The phylogenetic tree shows close relationship between NOOR strain and H. chrysospermus [MH854754-1], H. chrysospermus [MZ389105-1], H. chrysospermus [MK605327- 1], H. chrysospermus [MT595227-1], H. [EU816370-1], H. chrysospermus [MG685885-1]. The Iraqi isolate was recorded as NOOR strain in the National Centre for Biotechnology Information for the first time in Iraq. Keywords: Hypomyces chrysospermus, Phylogeny, DNA, Ribosomal, Biotechnology